Onion component, isoalliin, stimulates feeding and activates the arcuate nucleus neuropeptide Y, ghrelin- and Ninjin'yoeito-responsive neurons. (October 2021) - Wang, Lei; Han, Wanxin; Iwasaki, Yusaku; Yermek, Rakhat; Sharp, Geoffrey W.G.; Seino, Yutaka; Yada, Toshihiko
Abstract: Appetite loss or anorexia substantially decreases the quality of life in patients with cancer, depression and gastrointestinal disorders, and can lead to sarcopenia and frailty. Foods that restore appetite have been sought-for but are not currently available. Historically, onion intake was adopted to treat a variety of diseases with reduced appetite including cancer and gastrointestinal disturbances. While isoalliin is a core component of onion, the effects of isoalliin on feeding behavior and feeding centers remain unknown. Neuropeptide Y (NPY) and ghrelin are the most potent central and peripheral inducers of appetite. A Japanese kampo medicine Ninjin'yoeito activates ghrelin-responsive NPY neurons in the hypothalamic arcuate nucleus (ARC) and counteracts anorexia induced by an anti-cancer drug cisplatin. This study explored the effects of isoalliin on feeding behavior and activities of ARC neurons in mice. Isoalliin, injected intraperitoneally, dose-dependently increased food intake during dark phase (DP) and daily without altering light phase (LP) food intake. We measured cytosolic Ca 2+ concentration ([Ca 2+ ]i ) in single ARC neurons including NPY neurons identified by GFP fluorescence. Isoalliin increased [Ca 2+ ]i in 10 of 18 (55.6%) NPY neurons, a majority of which also responded to ghrelin with [Ca 2+ ]i increases, indicating that the ARC ghrelin-responsive NPY neuron is the major target of isoalliin. Isoalliin also increased [Ca 2+ ]i in the ARC neurons that responded to Ninjin'yoeito. These results indicate that isoalliin enhances feeding at the active period and activates ARC ghrelin-responsive NPY neurons and Ninjin'yoeito-responsive neurons. These abilities of isoalliin to stimulate DP feeding and activate ARC orexigenic neurons provide scientific evidence for the health beneficial effects of onion experienced historically and globally. Graphical abstract: Image 1 Highlights: Isoalliin, onion's core component, stimulates both dark phase and daily feeding in mice. Isoalliin activates ghrelin-responsive NPY neurons in hypothalamic arcuate nucleus (ARC). Isoalliin activates neurons in ARC that respond to Japanese kampo medicine Ninjin'yoeito. Isoalliin synergizes with ghrelin and Ninjin'yoeito to activate neurons in ARC. Isoalliin activates dark phase feeding and ARC neurons, possibly serving for health.